2022
DOI: 10.35891/ml.v13i1.2872
|View full text |Cite
|
Sign up to set email alerts
|

Tantangan dan Strategi Pemasaran Produk Halal di Indonesia

Abstract: The purpose of this study is to describe the challenges and marketing strategies of halal products produced by small and medium enterprises in Indonesia. The method used is a qualitative literature review method with primary data sources from interviews with BPJPH-LPH LPPOM MUI, East Java UMKM Service, UKM Service in 5 Regencies and Cities, namely Pasuruan Regency, Malang City, Batu City, Probolinggo City and Sidoarjo, while secondary data were obtained from supporting research documents, including journals, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…31 Disisi lain secara umum wakaf dikaji dari aspek hukum Islam. 32 Kajian wakaf dari sisi sosial keagamaan. 33 Studi-studi lain melihat wakaf secara umum dari perspektif hukum.…”
Section: Ulya Kencana Dan Gibtiah Model Pengelolaan Wakaf Produktif P...unclassified
“…31 Disisi lain secara umum wakaf dikaji dari aspek hukum Islam. 32 Kajian wakaf dari sisi sosial keagamaan. 33 Studi-studi lain melihat wakaf secara umum dari perspektif hukum.…”
Section: Ulya Kencana Dan Gibtiah Model Pengelolaan Wakaf Produktif P...unclassified
“…Halal business has a lot of potential to develop, especially in Indonesia (Muhammad Nizar & Antin Rakhmawati, 2022), (Mohamed, Zainalabidin, 2013) and (Abdalla Mohamed Bashir, 2019). Indeed, Indonesia's large Muslim population has implications for this great potential.…”
Section: Introductionmentioning
confidence: 99%
“…This potential can encourage economic growth by increasing the value of exports and foreign exchange reserves. It is following research conducted by (Muhammad Nizar & Antin Rakhmawati, 2022), (Sururi, 2021) and (Suyono, 2020), which found that Malaysia and the Uni Emirat Arab (UEA) are currently benefiting from the economic prosperity of their countries by establishing the halal industry, they are now industry leaders and the halal industry is no longer a complement to a nation's economic development.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of SMEs is fully supported by the government by providing various plans, programs, mechanisms and assistance (Rosyidah et al, 2019). Among other things, the formation of government agencies such as the M Service, Cooperative Office, Trade and Industry Office, government agencies really help SMEs in developing their business (Muhammad Nizar & Antin Rakhmawati, 2022). So that UKM actors together with the local regional government jointly develop businesses to improve people's welfare.…”
Section: A Introductionmentioning
confidence: 99%